La Some problems of accusation of the Criminal unfairness speaking of medical negligence - Vargas Pinto, Tatiana (Revista de derecho (Coquimbo. En línea), 2015)
The negative consequences to people’s life and health due to medical acts are frequent, and yet, the perpetrators are seldom liable or criminally accountable for the risks that such acts suppose and their curative purpose. This final aim explains why those negligent conducts are exceptional. Therefore, the criminal accountability in this sphere focuses in the exam of negligence. When can we talk about medical negligence? When can we charge a physician for the damaging consequences of his/her conduct? These are the main questions judges must solve and they face diverse difficulties such as: The precision of the duty of health care, the role of consent by the patient, the influence of the principle of reliability when team working, etc. These types of problems are managed in general, but also from the practical field.